Factors associated with postoperative hypothyroidism after lobectomy in papillary thyroid microcarcinoma patients. (February 2015) - Park, Ha Kyoung; Kim, Dong Wook; Ha, Tae Kwun; Choo, Hye Jung; Park, Young Mi; Jung, Soo Jin; Kim, Do Hun; Bae, Sang Kyun
ABSTRACT Purpose: No previous study regarding the correlation between post-operative thyroid function and underlying thyroid histopathology has been published. This study assessed the relationship between postoperative thyroid function after lobectomy and multiple factors in papillary thyroid microcarcinoma (PTMC) patients. Materials and methods: From January 2010 to December 2010, 338 patients who had undergone thyroid lobectomy for PTMC were enrolled. Patients with pre-operative hyperthyroidism or those with hypothyroidism but no pre-operative serological data were excluded, leaving a cohort of 285 patients. The relationships between post-operative thyroid function (based on successful cessation of thyroxine replacement therapy) and multiple factors (patient age and sex, serological data, the Pre-operative anteroposterior diameter of the thyroid gland, underlying histopathology of the thyroid gland, and number of attempts to stop thyroxine replacement therapy) were analyzed. Results: Out of 285 patients, 157 attempted to stop thyroxine replacement therapy once or twice after lobectomy; 91 successfully stopped thyroxine replacement therapy during the study period. The final histopathologic diagnoses after surgery included Hashimoto's thyroiditis (n = 5), non-Hashimoto type of lymphocytic thyroiditis (n = 17), and normal thyroid parenchyma (n = 135). Pre-operative thyroid-stimulating hormone (TSH) levels differed significantly between patients with postoperative hypothyroidism and those with postoperative euthyroidism (univariate logistic regression analysis, p = 0.0028; multivariate logistic regression analysis, p = 0.0029). No statistically significant differences were found for any other factors. Conclusions: The study results demonstrated that the Pre-operative TSH level was the only predictor for the development of post-operative hypothyroidism after thyroid lobectomy in PTMC patients.